COMPARATIVE PERFORMANCE ANALYSIS OF FISH FARMER PRODUCER ORGANIZATIONS IN FRESHWATER AQUACULTURE - SAHA , G. S.; DE, H. K.; SAHOO , B.; MAHAPATRA , A. S.; SREENIVASULU , G. (Journal of the Inland Fisheries Society of India, 2026)
This article documents the genesis and growth of FFPOs and compares the effectiveness of four FFPOs in Odisha using a set of seven indicators - viz., (a) Functioning efficiency (b) Increase in income (c) Increase in farmers’ share on consumers’ rupee (d) Inclusiveness (e) Sustainability of Farmers Producer Company (f) Level of satisfaction about the performance of FPC and (g) Empowerment. Maa Kharakhai (with an efficiency score of 57.3%) is the most efficient among the four FPOs studied. In terms of level of empowerment, level of satisfaction of members and increase in income, the score of Maa Kharakhai has left behind the other three FPOs. Year-wise growth in the number of Fish Farmer Producer Organizations (FFPOs) registered a steep rise from 2018, with the total reaching 192 by 2022. Karnataka tops the list and is closely followed by Uttar Pradesh, Tamil Nadu and Assam. Constraints that hinder the growth and performance of FFPOs are also identified.